Pyrazolo[4,3-c]pyridine Sulfonamides as Carbonic Anhydrase Inhibitors: Synthesis, Biological and In Silico Studies - Andrea Angeli; Victor Kartsev; Anthi Petrou; Boris Lichitsky; Andrey Komogortsev; Mariana Pinteala; Athina Geronikaki; Claudiu T. Supuran (MDPI AG, 2022)
Carbonic anhydrases (CAs, EC 4.2.1.1) catalyze the essential reaction of CO2 hydration in all living organisms, being actively involved in the regulation of a plethora of patho-/physiological conditions. A series of chromene-based sulfonamides were synthesized and tested as possible CA inhibitors. On the other hand, in microorganisms, the β- and γ- classes are expressed in addition to the α- class, showing substantial structural differences to the human isoforms. In this scenario, not only human but also bacterial CAs are of particular interest as new antibacterial agents with an alternative mechanism of action for fighting the emerging problem of extensive drug resistance afflicting most countries worldwide. Pyrazolo[4,3-c]pyridine sulfonamides were synthesized using methods of organic chemistry. Their inhibitory activity, assessed against the cytosolic human isoforms hCA I and hCA II, the transmembrane hCA IX and XII, and β- and γ-CAs from three different bacterial strains, was evaluated by a stopped-flow CO2 hydrase assay. Several of the investigated derivatives showed interesting inhibition activity towards the cytosolic associate isoforms hCA I and hCA II, as well as the 3β- and 3γ-CAs. Furthermore, computational procedures were used to investigate the binding mode of this class of compounds within the active site of hCA IX. Four compounds (1f, 1g, 1h and 1k) were more potent than AAZ against hCA I. Furthermore, compound 1f also showed better activity than AAZ against the hCA II isoform. Moreover, ten compounds out of eleven appeared to be very potent against the γ-CA from E.coli, with a Ki much lower than that of the reference drug. Most of the compounds showed better activity than AAZ against hCA I as well as the γ-CA from E.coli and the β-CA from Burkholderia pseudomallei (BpsCAβ). Compounds 1f and 1k showed a good selectivity index against hCA I and hCA XII, while 1b was selective against all 3β-CA isoforms from E.coli, BpsCA, and VhCA and all 3γ-CA isoforms from E.coli, BpsCA and PgiCA.